The governance of regulators in Latin America Evidence from the 2018 Indicators on the governance of sector regulators - Durand, Alexis (OECD Regulatory Policy Working Papers, 2020)
Using data from the 2018 OECD Indicators on the Governance of Sector Regulators, this paper analyses the governance of economic regulators in seven Latin American economies (Argentina, Brazil, Chile, Colombia, Costa Rica, Mexico and Peru) and across five critical network sectors (energy, e-communications, rail transport, air transport and water). The indicators allow for direct comparison of thirty economic regulators and provide a snapshot of the governance arrangements designed to preserve independence, practices to promote accountability, and the functions of the regulators. After describing key institutional characteristics of the regulators in the sample, the paper uses the indicators to identify patterns in governance. Evidence from in-depth performance reviews of regulators complements the indicators, shedding light on cost recovery fees, budgetary processes, and the use of advisory bodies in Latin American regulators